PROMOTING STUDENTS’ READING FLUENCY AND MOTIVATION THROUGH SHARED-READING WITH ANIMATED-VIDEO STORY - Cut Iqa Martia; Asnawi Muslem; Siti Sarah Fitriani (English Education Journal, 2020)
This research was conducted to investigate whether there was a significant difference in achievement between students who were taught by using Shared Reading with Animated Video Story and those who were not taught by using Shared Reading with Animated Video Story in reading fluency in terms of accurate reading, reading speed and reading expression, and the motivation toward the use of Shared Reading with Animated Video Story in reading fluency. This research was an experimental research. The population of the research comprised 129 students; samples of the research were 41 students from population by using  random sampling, 21 students in class 7C as experimental group, and 20 students in the class 7F as control group. The instruments used to collect the data were test and questionnaire. The data obtained from both instruments were analyzed by using SPSS 23 The post-test result of the experimental group showed that ttest (2.680) was higher than ttable (1.67). Further, utilizing independent samples t test, the sig. 2-tailed value (0,004) (0.05) confirmed that Ha was accepted and H0 was rejected. Moreover, the students had a quite positive responses (85%) toward the use of Shared Reading With Animated Video Story. To sum up, the implementation of shared reading strategy with animated video story is effective in improving students’ reading fluency and motivation. It is recommended that future related research should be conducted in more diverse educational settings to see how shared reading with animated video story is implemented.